France : 2002 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2002)
This 2002 Article IV Consultation highlights that the economy of France is facing a fast-approaching demographic turnaround-with the active population beginning to decline in 2007 and reducing annual per-capita-GDP growth by about half a percentage point for a few decades. In 2002, the general government budget deficit is expected to widen to 2.6 percent of GDP from 1.5 percent of GDP in 2001. The deterioration is in good part owing to the cyclical downswing but also to structural factors, in particular to the trend increase in social security spending.